Differentiation and response mechanisms of the endophytic flora of plants ecologically restored in the ilmenite area - Yu, Xin; Xu, Junqiang; Zou, Ziping; Zhang, Yunfeng; Wu, Peng; Li, Qiang (Frontiers in Microbiology, 2025)
Heavy metal contamination in soil is a serious environmental challenge, and abandoned mining areas are of particular concern. In order to rehabilitate the ecology of these areas. In this study, we used ICP-MS and potentiometric method to analyze the soil physicochemical and then endophytic bacteria of remediation plants with the help of 16sRNA sequencing, in order to investigate the ecological remediation of abandoned ilmenite mine and the effect of soil microbiology by seven common plants. The results revealed that the abandonment of ilmenite significantly increased the contents of total phosphorus, total potassium, available potassium, iron, and lead in the surrounding soils. It also affected the richness and diversity of endophytic bacterial communities. Pvi had the highest richness, while Tsi had the lowest richness (P < 0.05). A total of 28 phyla, 69 classes, 171 orders, and 521 genera were identified. A total of nine core OTUs were found: Stenotrophomonas, Chryseobacterium, Lactobacillus, Clostridium_sensu_stricto_12, Prevotella, Lactobacillus, Bradyrhizobium, Nocardioides, and Delftia. Beta diversity analysis revealed that the community structure of the endophytic bacteria differed during the remediation process at the ilmenite site. Functional prediction revealed upregulation of Dco transporter protein function, DNA-binding transcriptional regulators, glyoxalase or related metal-dependent hydrolases, acyl coenzyme A synthetases, ATPase components, amino acid synthesis, and cellular respiration-related functions. Pearson correlation analysis revealed that the SOC, TK, AN, AK, and Zn contents were significantly correlated with α diversity. Redundancy analysis (RDA) revealed that Actinobacteriota was significantly positively correlated with soil SOD, AN, TN, and TK contents. For the first time, this study revealed the interactions among plants, endophytic bacteria and soil pollutants, laying a theoretical basis for screening specific plant endophytic bacteria for ecological restoration.